Answer:
the answer is
Explanation:
To transform the graph of the function f(x) = -8x - 8 into the graph of g(x) = -x - 1, you need to apply a series of transformations. Here are the steps:
Horizontal Translation:
The function f(x) = -8x - 8 is a linear function, and to transform it into g(x) = -x - 1, you'll need to move the graph one unit to the right. This can be achieved by adding 1 to the x-values in the original function.
f(x) = -8(x + 1) - 8
Vertical Translation:
The next step is to move the graph one unit upward. This can be done by adding 1 to the whole function:
g(x) = -8(x + 1) - 8 + 1
g(x) = -8(x + 1) - 7
So to conclude the transformation from f(x) to g(x) consists of a horizontal translation of one unit to the right and a vertical translation of one unit upward. The final function g(x) is g(x) = -8(x + 1) - 7.
I hope this helps you please tell me if you find any errors or have any questions!
have a great day/night!